Review On Classical Management Of Female Infertility - Sah, Suman; choudhary, Susheela; Bharathi, K (International Research Journal of Ayurveda & Yoga, 2021)
Introduction -Infertility is defined as inability to conceive even after one year under normal marital relation without contraception. In Ayurveda, this condition is considered as Vandhyatva. The incidence of primary infertility is about 50% among women, while it is 25% among men, male and female factors together account for another 25%. Besides genetic factors, changed life style, increased stress, strain and environmental pollution are identified as factors contributing to the rising rate of infertility incidence. Material and methods- Brihatrayee, Laghutree, Kashyapa Samhita and other Ayurveda literatures, articles related to infertility are compiled. And various net sources,articles were explored. Results- This article explains Ayurvedic concept of Vandhyatva and various formulations used in Vandhyatva. Discussion-According to Ayurveda, important factors for conception are considered as Ritu (fertile period), Kshetra (uterus and reproductive organs), Ambu (Proper nutrition) and Bija (Shukra-Shonita) and also normalcy of Hridaya (Psychology). Abnormality of Vayu and Shatabhava (Matrja, Pitarja, Atmaja, Satvaja, Satmyaja and Rasaja), anyone of these cause infertilities (Vandhyatava). Both the Shodhana and Shamana chikitsa including Panchakarma is mentioned for infertility in Ayurvedic texts.